Converting Politics into History and History into Politics: La muerte no entrará en palacio by René Marqués. Issue 2 (3rd April 2017) - Ford, Katherine
ABSTRACT: The connection between history and politics is eternal. This intertwining is seen in the efforts of the stage to understand governmental history and to question past political decisions, efforts that are explored in René Marqués's La muerte no entrará en palacio . The Puerto Rican Marqués, a fierce advocate for Puerto Rican independence from the United States, wrote this play in 1959 as a denunciation of the creation of Puerto Rico's commonwealth status in 1952. Events that have shaped the political and social climate of 2017 in Puerto Rico underline the timeliness of Marqués's criticisms and necessitate another look at the play to understand Puerto Rico in the past and today.